Possible ionospheric preconditioning by shear flow leading to equatorial spread F - Hysell, D. L. (2005)
Vertical shear in the zonal plasma drift speed is apparent in incoherent and coherent scatter radar observations of the bottomside F region ionosphere made at Jicamarca from about 1600–2200 LT. The relative importance of the factors controlling the shear, which include competition between the E and F region dynamos as well as vertical currents driven in the E and F regions at the dip equator, is presently unknown. Bottom-type scattering layers arise in strata where the neutral and plasma drifts differ widely, and periodic structuring of irregularities within the layers is telltale of intermediate-scale waves in the bottomside. These precursor waves appear to be able to seed ionospheric interchange instabilities and initiate full-blown equatorial spread F. The seed or precursor waves may be generated by a collisional shear instability. However, assessing the viability of shear instability requires measurements of the same parameters needed to understand shear flow quantitatively - thermospheric neutral wind and off-equatorial conductivity profiles.